AN APPLICATION OF RESTORATIVES TO CHILDREN OF CRIMINAL OFFENDERS (STUDY AT POLDA NORTH SUMATRA) - Zarzani, T. Riza (Proceeding International Conference of Science Technology and Social Humanities, 2022)
The application of restorative justice and system diversion should be the main process or step in resolving disputes when children come into contact with the law. This study aims to find out how the application of the law regarding the application of a restorative justice system to children as perpetrators of criminal acts. Furthermore, to find out how the role of the Police in implementing the restorative justice system for children as perpetrators of crimes in the jurisdiction of the North Sumatra Regional Police. This research uses normative legal research methods and empirical legal research. That the arrangements regarding diversion and the restorative justice system are regulated in Article 6, Article 7 and Article 8..